Jual Beli Tanaman Monstera Adansonii di Indonesia Perspektif Hukum Islam - Febriyarni, Busra; Yarmunida, Miti; Asmara, Musda (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This study aims to analyze the sale and purchase of Monstera Adansonii plants in Indonesia according to Islamic law. This research is motivated by a phenomenon that occurs in Indonesian people buying and selling ordinary ornamental plants Monstera Adansonii at fantastic prices, even though these plants are not difficult to obtain, are not difficult to maintain, nor do they have extraordinary intrinsic value. The phenomenon of soaring crop prices is influenced by inflated prices by unscrupulous sellers and several parties they cooperate with and use good strategies so that the price of this plant soars (irrational). This study used a qualitative descriptive method, the data sources used were phenomena that occurred in the field and some news on the internet about the phenomenon of buying and selling Monstera Adansonii plants, the data analysis used deductive analysis. The result of this research is the sale and purchase of Monstera Adansonii plants which contain elements of fasid legal price engineering, even though they meet the principles and requirements of buying and selling in Islam, because there is an element of fraud by manipulating prices. This buying and selling includes buying and selling which is prohibited in Islamic law because it is included in the sale and purchase of najasy. From the maqashid syari’ah, buying and selling of monstera adansonii plants is included in the necessity of tahsiniyayyat, because this sale and purchase is not to meet primary or secondary needs and is in the ishraf category (excessive attitude in spending assets).